Evaluation of irrigant flow in the root canal isthmus region using a computational fluid dynamics model - Anchu Rachel Thomas; Dhanasekaran Sihivahanan; Ranjith Kumar Sivarajan (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study was to evaluate the irrigation dynamics of irrigant delivery systems and irrigating solutions in the root canal isthmus region of a mandibular premolar using computational fluid dynamics (CFD). Methods: A CFD model of the mandibular premolar with the root canal isthmus was created using scanned microcomputed tomography images. Using this CFD model, the irrigant flow in the root canal isthmus region was visualized. The irrigation dynamics of three irrigant delivery systems - Group 1: syringe irrigation (open-ended), Group 2: EndoVac irrigation system, and Group 3: modified EndoVac system were studied and compared to assess the efficiency. Following which, the wall shear stress, streamline of irrigant in the isthmus region, and irrigant velocity were evaluated. Results: Group 1 (open-ended needle) presented with the highest wall shear stress as compared to other groups, restricted to the apical third. All groups exhibited maximum velocity at the region of irrigant exit followed by a gradual decline in the isthmus and coronal region. It was observed that only Group III (Modified EndoVac) displayed a flow of irrigant in the isthmus region. Conclusions: The modified EndoVac system was efficient in delivering the irrigating solutions to the isthmus region.